BERSAMA KITA KENALI DAN CEGAH BULLYING DI SEKOLAH UNTUK MEMBENTUK KARAKTERISTIK SISWA PADA SMP PLUS AL-ISLAMIYAH TANGERANG SELATAN - Sunarto, Ading; Agrasadya, Agrasadya; Tanjung, Asridah Warni (Yayasan Education and Social Center, 2024)
Education is an effort to transfer knowledge so as to form the development of a person's potential which is ultimately able to survive in real life. In essence, education is a basic human need that will later form a civilization with intellectuality. In general, bullying is an act of physical or psychological violence carried out by perpetrators who have power over weaker victims, causing feelings of depression, stress and prolonged trauma, usually occurring continuously. There is no common definition of the term bullying. Identification of problems in this community service, namely, reviewing the picture of bullying, reviewing the impact of bullying on victims and perpetrators, reviewing public perceptions of bullying and analyzing bullying and finding optimal solutions to eradicate bullying. The purpose of this PKM program is to provide an understanding related to providing information that even the smallest act of bullying can have a negative impact on both victims and perpetrators. Providing information that bullying is inappropriate in educational institutions or in the community. Eradicating a moral crisis such as bullying in educational institutions is clearly not an easy matter. However, if bullying is allowed to continue to occur and become rooted so that it increases irrationality, especially in educational environments, then there will be a shift in the values ??of violence (bullying) from what should not be good to do to being common and appropriate to do in educating students. In fact, bullying has a very detrimental impact on social life, children's psychological development, norms, and the future of the nation. Therefore, anti-bullying efforts require support from all components of society starting from the family, school, and environment